2019
DOI: 10.1111/jvim.15568
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta‐analyses of the association between 4 mycoplasma species and lower respiratory tract disease in dogs

Abstract: Background The pathogenic role of mycoplasmas in the lower respiratory tract (LRT) of dogs is debated, because mycoplasmas can be isolated from both healthy and sick dogs. Objectives To critically assess available data from controlled observational studies on the role of 4 mycoplasma species in LRT disease of dogs. Design Systematic review and meta‐analyses. Methods Seven electronic databases were searched for relevant publications. Risk of bias was assessed by the Newcastle‐Ottawa Scale. Meta‐analyses, strati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…Since then M. cynos has been detected in many other cases of CIRDC, often concurrently with viral infections, confounding the interpretation of its role in the pathogenesis of CIRDC (reviewed by Priestnall et al, 2014;Maboni et al, 2018). However, Zeugswetter et al (2007 reported an outbreak of M. cynos monoinfection in a litter of 3-week-old golden retriever pups and a recent study supports the role of M. cynos as a primary pathogen in the lower respiratory tract (Jambhekar et al, 2019).…”
Section: Biology and Pathophysiology Of Pathogens In Cirdcmentioning
confidence: 95%
“…Since then M. cynos has been detected in many other cases of CIRDC, often concurrently with viral infections, confounding the interpretation of its role in the pathogenesis of CIRDC (reviewed by Priestnall et al, 2014;Maboni et al, 2018). However, Zeugswetter et al (2007 reported an outbreak of M. cynos monoinfection in a litter of 3-week-old golden retriever pups and a recent study supports the role of M. cynos as a primary pathogen in the lower respiratory tract (Jambhekar et al, 2019).…”
Section: Biology and Pathophysiology Of Pathogens In Cirdcmentioning
confidence: 95%
“…The incubation period of MP infection is 1–3 weeks or more, and the severity of lung inflammation varies in different children. In recent years, studies all over the world have shown that MP infection can not only cause respiratory symptoms, but also cause pulmonary complications, hypoxemia, and multi-system functional damage such as circulation, digestion, and nerves, and even endanger life, seriously reducing children’s quality of life and life safety ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 99%
“…Mycoplasma cynos has previously been identified in one cat with conjunctivitis, though more research is required to understand its pathogenic potential (29). By comparison Mycoplasma cynos has been identified in samples from dogs with respiratory disease (30,31). Influenza virus remains a relatively rare occurrence in American cats and has primarily been associated with outbreak situations or spillover events and was not expected to be found in this study (32)(33)(34).…”
Section: Discussionmentioning
confidence: 70%